SISTEM PEMANTAUAN PENGGUNAAN PROTOKOL KESEHATAN COVID-19 MENGGUNAKAN METODE HAAR CASCADE DAN NEURAL NETWORK - Alif Yudhistira Putra Bayu; Suroso; Sholihin (Jurnal Qua Teknika, 2021)
SISTEM PEMANTAUAN PENGGUNAAN PROTOKOL KESEHATAN COVID-19 MENGGUNAKAN METODE HAAR CASCADE DAN NEURAL NETWORK COVID-19 is the biggest health problem that occurs in the world today, this virus with its rapid spread and strong resistance has claimed many lives. One way to prevent the rapid spread of this virus is to break the chain of its spread, and always complying with the COVID-19 Health protocol. Some examples of the COVID-19 Health Protocol are the use of masks, normal body temperature, always washing hands, and others. However, public awareness of compliance is still very low, so the COVID-19 pandemic has not ended until now. The best solution at this time is to monitor and ensure the use of the COVID-19 Health protocol. However, with the advancement of technology now and minimizing human contact, the author created a MONITORING SYSTEM FOR THE USE OF COVID-19 HEALTH PROTOCOL USING HAAR CASCADE AND NEURAL NETWORK METHODS that use machine learning technology so that there will be no contact between humans. With this tool, the author hopes that it can reduce the spread of COVID-19 and can end it so that all people can return to normal activities without being disturbed by virus disturbances.